Kuwait Food Company (Americana) : financial analysis - Mehta, Anupam; Lulla, Karuna (London : SAGE Publications Pvt. Ltd, 2016)
This case makes an attempt to carry out financial analysis of the performance of Kuwait Food Company with a view to understand if it would be worth investing in it. The case is developed from the perspective of Mohd Hussain, a small investor in Kuwait, who had already lost heavily in speculative investment. Being from a commerce background, he decided to apply his learning from a finance masters class. As he started to explore the company, he was puzzled with the financials of the company. Although Americana's share prices had increased, the company's finances were not so impressive. The sales of the company had been increasing in the last three quarters, but the net profit had gone down over the previous few years from KWD 54 million in the year 2011 to KWD 50 million in the year 2012. Even the margins were squeezed for the recent three quarters in 2013. With this information, Hussain knew that several answers were needed before making the investment choices. Was the growth of Americana's share prices a speculative mania, or did it actually represent value? What were the issues with Americana's profitability? How was the overall financial health of the business?
Originally published in Mehta, A., & Lulla, K. (2016). Kuwait Food Company (Americana): Financial analysis. South Asian Journal of Business and Management Cases, 5(2), 168-180. DOI:.
Includes bibliographical references and index.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Kuwait Food Company (Americana) -- Finance -- Case studies; Business enterprises -- Finance -- Case studies; Industrial management -- Case studies; Food industry and trade